3x+40=-2(-1+8x)

Simple and best practice solution for 3x+40=-2(-1+8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+40=-2(-1+8x) equation:


Simplifying
3x + 40 = -2(-1 + 8x)

Reorder the terms:
40 + 3x = -2(-1 + 8x)
40 + 3x = (-1 * -2 + 8x * -2)
40 + 3x = (2 + -16x)

Solving
40 + 3x = 2 + -16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '16x' to each side of the equation.
40 + 3x + 16x = 2 + -16x + 16x

Combine like terms: 3x + 16x = 19x
40 + 19x = 2 + -16x + 16x

Combine like terms: -16x + 16x = 0
40 + 19x = 2 + 0
40 + 19x = 2

Add '-40' to each side of the equation.
40 + -40 + 19x = 2 + -40

Combine like terms: 40 + -40 = 0
0 + 19x = 2 + -40
19x = 2 + -40

Combine like terms: 2 + -40 = -38
19x = -38

Divide each side by '19'.
x = -2

Simplifying
x = -2

See similar equations:

| 3b-2b=-1 | | Px+12=17forx | | (q-10)*3=27 | | 15a-26=6a+1 | | 3(4-6)=5(x+8) | | n*5+210=n*13-6 | | 7z+11=z+17 | | 12=ps | | -2x-95-8x=55 | | 3g(3x-4)-3)/f(3(2x^2-3x) | | -2x^2+24x-72= | | 20w/410 | | (2x-3)-2(3x+2)=-4(x+1) | | -200b^2+2a^2= | | -3x-51+9x=51 | | x-155(1/155) | | -3x^2+30x-75= | | 5x+3z=-1 | | s(t)=63-16t^2 | | 25+3(z-7)+2(9-z)=z | | 4a-4a^2+8= | | tan51=18/x | | 6n+9=-11 | | 3f(x)+g(2x)= | | f(5x-8)=2x-1 | | H(t)=2+46.5t-3.5t^2 | | sinx=6cosx | | -162+2x^2= | | sin(30)=X/4 | | 1/2X1/8 | | 85=5v-9 | | 1/2X1/12 |

Equations solver categories